The Role of Host Genetic Signatures on Root–Microbe Interactions in the Rhizosphere and Endosphere - Yu, Peng; Hochholdinger, Frank (Frontiers in plant science, 2018)
Microbiomes inhabiting plants are crucial for plant productivity and well-being. A plethora of interactions between roots, microbiomes, and soil shapes the self-organization of the microbial community associated with the root system. The rhizosphere (i.e., the soil close to the root surface) and endosphere (i.e., all inner root tissues) are critical interfaces for the exchange of resources between roots and the soil environment. In recent years, next-generation sequencing technologies have enabled systemic studies of root-associated microbiomes in the endosphere and interactions between roots and microbes at the root-soil interfaces. Genetic factors such as species and genotype of host plants are the driving force of microbial community differentiation and composition. In this mini-review, we will survey the role of these factors on plant-microbe interactions by highlighting the results of next-generation genomic and transcriptomic studies in the rhizosphere and endosphere of land plants. Moreover, environmental factors such as geography and soil type shape the microbiome. Relationships between the root-associated microbiome, architectural variations and functional switches within the root system determine the health and fitness of the whole plant system. A detailed understanding of plant-microbe interactions is of fundamental agricultural importance and significance for crop improvement by plant breeding.